Evaluasi User Experience Menggunakan meCUE Questionnaire (Studi Kasus Pada Aplikasi Traveloka Dan Pegipegi) - Ricco Anjasmara Putra Pratama; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Traveloka and Pegipegi is an application as a service provider that accommodates the distribution of alternative airline tickets for airplane ticket sales online. The number of users of a product or application, certainly does not guarantee user experience satisfaction from an application. The Framework meCUE Questionnaire is a framework used in the process of evaluating a UX on a website or application. meCUE Questionnaire is suitable to be used in all types of User experience assessments on one or several interactive and trusted systems to analogize a variety of products and examine various changes in design experience for long-term use. This study aims to evaluate the user experience of the application using the meCUE questionnaire method in order to find out whether the user experience has been felt good or not, and which aspects of the user experience are still not good. meCUE questionnaire consists of 4 modules, namely Module I (product perceptions), Module II (user emotions), Module III (Consequences of use) and Module IV (overall evaluation) with a total of 34 item statements. The first stage in this study was to translate the meCUE questionnaire and then distribute it to 60 respondents. Furthermore, the results obtained from the questionnaire were calculated on the meCUE questionnaire so that the results of the UX evaluation can be found. The results of the calculation of the highest average value for Traveloka are 5.90 (usefulness), and the lowest average value of 2.49 (negative emotions), in the Pegipegi application the highest average value is 5.08 (usefulness), and the value the lowest average of 2.48 (negative emotions). The average for the overall score is 5.8 for Traveloka and 4.5 for Pegipegi